Harambee: Pulling it All Together. Issue 1 (January 2017) - Dixson, Adrienne D.; Ladson-Billings, Gloria
The articles in this special issue represent both our attempt as editors to survey the field and provide some clarity for practitioners and teacher educators on fundamental ideas that frame CRP, not to limit its implementation or future research directions, but to ensure that as a community of educators and scholars, we share a common understanding of exactly what it means to be culturally relevant. The articles in this special issue provide both that clarity of the field, and vision for the future.